Sexual harrasment at clinical placement : impact towards female nursing student - Siti Ayusafura, bt Muzamil (Faculty of Medicine & Health Sciences, 2008)
This research investigated on the nature of existence and extent of sexual harassment among female nursing students of University Malaysia Sarawak. However the main point to look into the impact from sexual harassment towards nursing students. A booklet of questionnaire made based on various literatures was administered to 75 total number of female nursing students from year two to year four.